Perbandingan hasil belajar trigonometri dengan model pembelajaran konvensional dan model pembelajaran kooperatif jigsaw - Meitria Laily Azizah; Hendro Permadi (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
Selection of learning models is important for improving student learning outcomes. This study aims to compare the results of trigonometric learning with conventional learning models and Jigsaw cooperative learning models and also want to know results of trigonometric learning with conventional learning and Jigsaw cooperativ learning. This type of research is experimental research with quantitative methods. The data collected in this study include: 1) the value of the pre test experimental class 1 (Jigsaw cooperative learning model) and the experimental class 2 (conventional learning models), 2) the value of the two post test classes, 3) the assessment of the skills of the two classes. The results of the analysis of the combined difference in the value of post test and skills assessment with the two pre test values ​​of the two classes using the 2 Sample Independent t-test showed that the sig (2-tailed) value was 0.003 or less than the significant level of 0.05. So it can be concluded that there are differences in learning outcomes by applying conventional learning models and Jigsaw cooperative learning models on trigonometric comparison material on right triangles in Batu city MAN. It is evident from the combined value difference between post test and skills assessment with the experimental class 1 pre test score of 65.86 while the experimental class 2 is 52.96. Pemilihan model pembelajaran adalah hal yang penting untuk meningkatkan hasil belajar siswa. Penelitian ini bertujuan untuk mengetahui perbandingan hasil belajar trigonometri dengan model pembelajaran konvensional dan model pembelajaran kooperatif Jigsaw serta ingin mengetahui hasil belajar trigonometri dengan diterapkan model pembelajaran konvensional dan model pembelajaran kooperatif Jigsaw. Jenis penelitian ini adalah penelitian eksperimen dengan metode kuantitatif. Data yang dikumpulkan pada penelitian ini meliputi: 1) nilai pre test kelas eksperimen 1 (model pembelajaran kooperatif Jigsaw) dan kelas eksperimen 2 (model pembelajaran konvensional), 2) nilai post test kedua kelas, 3) penilaian keterampilan kedua kelas. Hasil analisis dari selisih gabungan nilai post test dan penilaian keterampilan dengan nilai pre test kedua kelas menggunakan uji 2 Sample Independent t-test menunjukkan bahwa nilai sig(2-tailed) sebesar 0,003 atau kurang dari taraf signifikan yaitu 0,05. Sehingga dapat disimpulkan bahwa ada perbedaan hasil belajar dengan menerapkan model pembelajaran konvensional dan model pembelajaran kooperatif Jigsaw pada materi perbandingan trigonometri pada segitiga siku-siku di MAN kota Batu. Terbukti pada selisih nilai gabungan post test dan penilaian keterampilan dengan nilai pre test kelas eksperimen 1 sebesar 65,86 sedangkan kelas eksperimen 2 sebesar 52,96.